The informal sector in eThekwini, South Africa: Challenges, opportunities and pathways to formalisation - Marsha Gabriel; Krishna Govender (Universitas Nusa Cendana, 2026)
Against a backdrop of persistent unemployment and constrained access to formal labour markets, informal trading continues to function as a critical livelihood strategy for marginalised populations in South Africa. This study critically examines the challenges and opportunities associated with the informal sector in the Durban Central Business District (CBD). Adopting a qualitative descriptive design, the research explores the perspectives of three key stakeholder groups: government representatives, local communities, and informal traders. The findings reveal enduring structural, regulatory, and socio-economic barriers that hinder effective formalisation and sustainable sectoral development, despite the existence of policy interventions aimed at supporting informal economic activities. In addition, the study identifies gaps in stakeholder coordination, regulatory implementation, and urban governance that constrain the sector’s contribution to inclusive economic growth. Based on these findings, the study proposes a conceptual framework to guide collaborative stakeholder engagement and enhance the developmental and economic potential of the informal sector. The study contributes to the broader discourse on urban informality, inclusive development, and policy implementation in emerging economies by providing context-specific insights into the dynamics of informal trading in urban South Africa. Keywords: Informal Economy; Formalisation; Economic Development; Unemployment